2014
DOI: 10.1093/nar/gku1232
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 nucleocapsid and ESCRT-component Tsg101 interplay prevents HIV from turning into a DNA-containing virus

Abstract: HIV-1, the agent of the AIDS pandemic, is an RNA virus that reverse transcribes its RNA genome (gRNA) into DNA, shortly after its entry into cells. Within cells, retroviral assembly requires thousands of structural Gag proteins and two copies of gRNA as well as cellular factors, which converge to the plasma membrane in a finely regulated timeline. In this process, the nucleocapsid domain of Gag (GagNC) ensures gRNA selection and packaging into virions. Subsequent budding and virus release require the recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 74 publications
3
43
0
Order By: Relevance
“…The increase in virion release triggered by EAP45 rescue is, however, not dependent on the presence of an active protease ( Figure 9), suggesting the rescue effect of EAP45 in EAP45 KO cells is independent of virion maturation, and that budding neck closure precedes the activation of the viral protease. Our data are consistent with the notion that in EAP45 KO cells, recruitment of EAP45 is required to restore defective budding kinetics and to facilitate the sealing of the budding neck so that the activated protease is confined within the budding virions to allow Gag maturation to proceed (Bendjennat & Saffarian, 2016;Chamontin et al, 2015). The significant correlation between the final cleavage of Gag and virion release also supports this notion ( Figure 10).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The increase in virion release triggered by EAP45 rescue is, however, not dependent on the presence of an active protease ( Figure 9), suggesting the rescue effect of EAP45 in EAP45 KO cells is independent of virion maturation, and that budding neck closure precedes the activation of the viral protease. Our data are consistent with the notion that in EAP45 KO cells, recruitment of EAP45 is required to restore defective budding kinetics and to facilitate the sealing of the budding neck so that the activated protease is confined within the budding virions to allow Gag maturation to proceed (Bendjennat & Saffarian, 2016;Chamontin et al, 2015). The significant correlation between the final cleavage of Gag and virion release also supports this notion ( Figure 10).…”
Section: Discussionsupporting
confidence: 90%
“…The timing of this process is believed to be critically important to maintain proper virion maturation and virion infectivity. Delayed budding caused by late domain or NC mutation leaves the virus budding neck open allowing the activated protease to diffuse back into the cytosol (Bendjennat & Saffarian, 2016;Chamontin et al, 2015). This loss of protease is thought to be instrumental in producing the maturation defect observed in budding defective viruses.…”
Section: Discussionmentioning
confidence: 99%
“…1b). As previously reported264546, mutating the NC ZF motifs modified Gag processing as evidenced by the accumulation of p41 MA/CA/SP1 precursor (Fig. 1b).…”
Section: Resultssupporting
confidence: 83%
“…Moreover, it was reported that the deletion of the distal ZF2 led not only to abnormal uptake of Tsg101, but also to biogenesis defects during virion formation (83). It is thus possible that the observed delay of GagZF1 or GagZF2 to reach the PM (Figure 4) is related to their defective recruitment of the ESCRT machinery.…”
Section: Discussionmentioning
confidence: 96%